A review of NeuroAiDTM II (MLC901) development in Alzheimer’s disease treatment: promises of a multimodal pathway - Dib, Michel; Ampil, Encarnita; Kee, Hoo Fan; Krespi, Yakup; Al Mahdawi, Akram; Ogun, Shamsideen Abayomi; Pakdaman, Hossein; Rejdak, Konrad (Scientific Research and Community Ltd, 2022)
Background: Alzheimer’s disease (AD) is a clinical and economic burden on society. Without new treatment, the impact of AD on society could triple by 2050. Aim: After a brief overview of treatments and challenges of new drug developments for AD, we reviewed the preclinical and clinical development program of NeuroAiD (MLC901, MLC601). Method: A literature search was conducted by using different web sources. The initial screening was based on keywords contained in the subtitles of each corresponding paragraphs of this article. We sorted the reviewed publications by relevance and publication date selecting 74 references out of the 319 initially shortlisted for review. Review: Since 1998, only symptomatic drugs were marketed. Intensive research has continued, aimed at delaying the onset of the disease and/or slowing its progression. However, the predictive value of delaying the onset of AD remains debated. Since 2003, aducanumab is the first new treatment approved and registered by US-FDA as an amyloid beta-directed antibody indicated for the treatment of Alzheimer’s disease under post-marketing conditions. Traditional medicines (TM) have shown interesting results, but many of TM clinical studies leave much to be desired from a methodological point of view. Among TM, NeuroAiD (MLC901/601), a botanical-derived combination, acts in a multimodal pathway combining neuroprotective and neuroregenerative properties. It has demonstrated sustained symptomatic benefits, slowing the disease progression in AD with a good safety profile. Discussion/Conclusions: The discovery of treatments preventing or slowing down the disease progression, are necessary to get reliable diagnostic tools to confirm AD diagnosis, and follow its evolution and long-term therapy. A growing consensus is emerging on the need for a multi-factorial approach to the treatment and the development of suitable AD drug combinations. Such an approach has been that of TM for a long time. This is the case for NeuroAiD, that it may be integrated safely either after symptomatic treatments have failed or on top of symptomatic treatments.